Systematics of the hypervariable Moraea tripetala complex (Iridaceae: Iridoideae) of the southern African winter rainfall zone - Goldblatt, Peter; Manning, J.C. (African Biodiversity & Conservation, 2012)
Field and laboratory research has shown that the Moraea tripetala complex of western South Africa, traditionally treated as a single species, sometimes with two additional varieties, has a pattern of morphological and cytological variation too complex to be accommodated in a single species. Variation in floral structure, especially the shape of the inner tepals, degree of union of the filaments, anther length and pollen colour form coherent patterns closely correlated with morphology of the corm tunics, mode of vegetative reproduction, and in some instances capsule and seed shape and size. The morphological patterns also correlate with geography, flowering time and sometimes habitat. It is especially significant that different variants of the complex may co-occur, each with overlapping or separate flowering times, a situation that conflicts with a single species taxonomy. We propose recognizing nine species and three additional subspecies for plants currently assigned to M. tripetala. M. grandis, from the western Karoo, has virtually free filaments and leaves often ± plane distally; closely allied M. amabilis, also with ± free filaments and often hairy leaves, is centred in the western Karoo and Olifants River Valley. Its range overlaps that of M. cuspidata, which has narrowly channelled, smooth leaves, linear inner tepals spreading distally and filaments united for up to 1.5 mm. M. decipiens from the Piketberg, M. hainebachiana, a local endemic of coastal limestone fynbos in the Saldanha District, M. ogamana from seasonally wet lowlands, and early flowering M. mutila constitute the remaining species of the complex in the southwestern Western Cape. M. helmei, a local endemic of middle elevations in the Kamiesberg, Namaqualand, has small flowers with short, tricuspidate inner tepals. All but M. amabilis and M. mutila are new species. We divide M. tripetala sensu stricto into three subspecies: widespread subsp. tripetala, subsp. violacea from the interior Cape flora region, and late-flowering subsp. jacquiniana from the Cape Peninsula and surrounding mountains.